ANALISIS PERUBAHAN PENDAPATAN PEDAGANG MASKER ECERAN AKIBAT PANDEMI COVID-19 - Putri, Evita M. C.; Bangun, Aron Karolina; Makalalag, Afiansyah; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2021)
Covid-19 really makes the world feel a crisis in all things, namely the economy, education, health, and many more. However, Covid-19 has made the demand for masks greatly increased from before the existence of Covid-19. Because every human being needs a mask to prevent being exposed to the Covid-19 virus, so that retail mask traders are also affected. We take an example for retail mask traders in the Pinasungkulan market, Karombasan, Manado City. We interviewed 22 respondents who work as mask retailers. We questioned the income before and after the Covid-19 pandemic, as well as the prices of the types of masks before and after the Covid-19 pandemic.